Phytochemical Study And Antibacterial Activity Of Different Extracts Of Pistacia Lentiscus L Collected From Dahra Region West Of Algeria - Missoun, F.; Bouabedelli, F.; Benhamimed, E.; Baghdad, A.; Djebli, N. (University of Eloued جامعة الوادي, 2017)
The purpose of this study was to investigate the phytochemical proprieties, antioxidant and antibacterial activities of different extracts of Pistacia lentiscus on two pathogenic bacteria. The concentration of total phenols was analyzed using Folin-Ciocalteu’s method. Exracts of plant were evaluated for their antimicrobial activities against Staphylococcus aureus and Esherichia coli using the agar disk diffusion method and the minimal inhibitory concentration. The phytochemical study revealed the presence of major bioactive chemical constituents in different extracts of P. lentiscus (flavonoids, alkaloids, saponins, tannins, terpenoids, glycosides and steroids). Results showed that this plant has antioxydant activity and high quantity of total phenols and flavonoids. Antibacterial activity of the aerial parts of P. lentiscus against tested bacteria has shown that Gram-negative strains were more resistant compared to the Gram- positive ones. We can conclude that Pistacia lentiscus from Dahra region under investigation can be a potential source of useful drugs.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 02
Keywords: Pistacia lentiscus; Phytochemicals; total phenol; Flavonoids; Antibacterial activity.